The Comparison of Analytical Methods for Determination of Eugenol Content in Water Soluble Base from Clove Flower (Syzygium aromaticum) Essential Oil Ointment using UV-Vis Spectrophotometry and High Performance Liquid Chromatography - Puput Herawati Said Hasan; Nining Sugihartini; Hari Susanti (Jurnal Biologi Tropis, 2023)
The eugenol content in clove essential oil can be used as a parameter to determine the chemical stability of clove essential oil ointment. Both UV- Vis and HPLC spectrophotometry methods can be used to determine eugenol levels. However, no studies have compared the two methods. This study aims to find out which analytical method is more valid in determining the eugenol content of clove flower essential oil (Syzygium aromaticum) in water-sea based ointments, between the UV-Vis spectrophotometric method and the HPLC method. The parameters in the validation of the analytical method carried out include parameters of linearity, selectivity, precision, accuracy, limit of detection (LOD) and limit of quantification (LOQ). The results of method validation using UV spectrophotometry showed linearity (R = 0.9998), precision (CV = 0.137%), LOD 0.190 µg/mL, LOQ 0.632µg/mL, accuracy (recovery = 100.05%). Method validation using HPLC produced parameters of linearity (R= 0.998), precision (CV = 0.533%), LOD 0.28 µg/mL, LOQ 0.93 µg/mL, accuracy (recovery = 106.43. Average levels of eugenol in water-soluble base MABC ointment using UV spectrophotometry (% concentration = 2.201 ± 0.037) while using HPLC (% concentration = 3.191 ± 0.023). Both methods met the validation requirements. The assay results using both methods met the requirements according to the Indonesian Pharmacopoeia Edition VI. The two methods did not have a significant difference based on the student test, both in the validation parameters and the results of determining the levels of eugenol.